Basal insulin initiation in primary vs. specialist care: similar glycaemic control in two different patient populations. Issue 3 (24th February 2016) - Orozco‐Beltran, D.; Pan, C.; Svendsen, A. L.; Færch, L.; Caputo, S.; ,
Summary: Objective: To investigate the effect of healthcare provider (HCP) type (primary vs. specialist) on glycaemic control and other treatment parameters. Research design and methods: Study of Once‐Daily Levemir (SOLVE ™ ) is an international, 24‐week, observational study of insulin initiation in people with type 2 diabetes. Results: A total of 17, 374 subjects were included, comprising 4144 (23.9%) primary care subjects. Glycaemic control improved in both HCP groups from baseline to final visit [glycated haemoglobin (HbA1c) −1.2 ± 1.4% (−13.1 ± 15.3 mmol/mol) and −1.3 ± 1.6% (−14.2 ± 17.5 mmol/mol), respectively]. After adjustment for known confounders, there was no statistically significant effect of HCP group on final HbA1c [−0.04%, 95% confidence interval (CI) −0.09 to −0.01 (−0.4 mmol/mol, 95% CI −1.0−0.1 mmol/mol), p = 0.1590]. However, insulin doses at the final visit were higher in primary care patients (+0.06, 95% CI 0.06–0.07 U/kg, p < 0.0001). Logistic regression demonstrated a significant effect of HCP type (primary vs. specialist care) on hypoglycaemia risk [odds ratio (OR) 0.75, 95% CI 0.64–0.87, p = 0.0002]. Primary care physicians took more time to train patients and had more frequent contact with patients than specialists (both p < 0.0001). Conclusions: Primary care physicians and specialists achieved comparable improvements in glycaemic control following insulin initiation.